“Proximity” in organic food products sourcing channels in the Grande Florianópolis region – SC – Brazil: A “proximidade” nos circuitos de abastecimento de alimentos orgânicos da Grande Florianópolis – SC – Brasil - Gelbcke, Daniele Lima; Rover, Oscar José; Brightwell, Maria das Graças Santos Luiz; da Silva, Clécio Azevedo; Viegas, Mauricio da Trindade (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2018)
Geographic proximity between food production and consumption has been largely emphasized as positive, but there is little empirical evidence on how short food circuits (especially when they involve retailing) are organized and to what extent they are actually rooted in regional economies. This article seeks to critically examine the geographical and/or relational proximity parameters commonly discussed in the debate about short food circuits, examining the production and commercialization of organic foods in the Greater Florianopolis region, focusing mainly on the regional dimension of this circulation. By bringing empirical evidence - through interviews with actors involved in production, processing and marketing as well as quantitative research in various retail outlets we show that supermarkets are the main distribution channel and that demand for organic manufactured and off-season products is not met by regional sources. Geographic proximity offers advantages both to producers and consumers, such as lower energy costs in transportation, freshness, as well as the possibility of relating directly to consumers. We also found that intermediaries, be it a farmer or a processer, are important players in the social construction of regional markets but extends the number of actors in the chain, increasing the distance between producers and consumers.Keywords: proximity; organics; marketing; short food circuits; Florianópolis.GELBCKE, Daniele Lima; ROVER, Oscar José; BRIGHTWELL, Maria das Graças Santos Luiz; SILVA, Clécio Azevedo da; VIEGAS, Mauricio da Trindade. A “proximidade” nos circuitos de abastecimento de  alimentos orgânicos da Grande Florianópolis – SC – Brasil. Estudos Sociedade e Agricultura, v. 26, n. 3, p. 539-560, out. 2018.Submitted in may 2018.Accepted in september 2018.